Peran Agama terhadap Ide Bunuh Diri pada Mahasiswa Religius - Ifenta, Alfie; Pratiwi, Lila (Institut Agama Islam Negeri Kerinci, Indonesia, 2025)
Suicidal ideation is a psychological problem where it can be caused by various factors as well as various impacts that influence it including religion. This study aims to look at the role of religion on suicidal ideation in religious students and focuses on seeing the role of religion as a protective factor or as a factor that increases the risk of suicidal ideation. This research uses a qualitative approach with phenomenological methods so that the subject's experience can be explored more deeply. Data will be collected using interviews with religious students who have had or are having suicidal ideation where religiosity will be measured using the Muslim Religiosity Scale by Amir (2021) as well as using interview guidelines based on Pargament's theory (1998) and the interview process is only carried out on relevant informants. This study uses data analysis techniques in the form of thematic analysis. The results found that the role of religion can be a protective factor and can also be a risk factor for suicidal ideation.